Achieving universal health coverage and sustainable development goals by 2030: investment estimates to increase production of health professionals in India - Anup Karan; Himanshu Negandhi; Mehnaz Kabeer; Tomas Zapata; Dilip Mairembam; Hilde De Graeve; James Buchan; Sanjay Zodpey (Hum. Resour. Health, 2023)
BackgroundCOVID-19 has reinforced the importance of having a sufficient, well-distributed and competent health workforce. In addition to improving health outcomes, increased investment in health has the potential to generate employment, increase labour productivity and foster economic growth. We estimate the required investment for increasing the production of the health workforce in India for achieving the UHC/SDGs.MethodsWe used data from National Health Workforce Account 2018, Periodic Labour Force Survey 2018-19, population projection of Census of India, and government documents and reports. We distinguish between total stock of health professionals and active health workforce. We estimated current shortages in the health workforce using WHO and ILO recommended health worker:population ratio thresholds and extrapolated the supply of health workforce till 2030, using a range of scenarios of production of doctors and nurses/midwives. Using unit costs of opening a new medical college/nursing institute, we estimated the required levels of investment to bridge the potential gap in the health workforce.ResultsTo meet the threshold of 34.5 skilled health workers per 10 000 population, there will be a shortfall of 0.16 million doctors and 0.65 million nurses/midwives in the total stock and 0.57 million doctors and 1.98 million nurses/midwives in active health workforce by the year 2030. The shortages are higher when compared with a higher threshold of 44.5 health workers per 10 000 population. The estimated investment for the required increase in the production of health workforce ranges from INR 523 billion to 2 580 billion for doctors and INR 1 096 billion for nurses/midwives. Such investment during 2021-2025 has the potential of an additional employment generation within the health sector to the tune of 5.4 million and to contribute to national income to the extent of INR 3 429 billion annually.ConclusionIndia needs to significantly increase the production of doctors and nurses/midwives through investing in opening up new medical colleges. Nursing sector should be prioritized to encourage talents to join nursing profession and provide quality education. India needs to set up a benchmark for skill-mix ratio and provide attractive employment opportunities in the health sector to increase the demand and absorb the new graduates.
Keywords: Tuberculosis/prevention and control; Systematic screening; Vulnerable populations; Health care costs; Health equity